2005
DOI: 10.1002/syn.20143
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of NMDA receptor NR2A and NR2B subunits in the acute intoxicating effects of ethanol in mice

Abstract: The present study examined the roles of NR2A and NR2B subunit-containing NMDA receptors in the mediation of the sedative/hypnotic effects of ethanol in mice. The ability of the competitive NMDA antagonist, CGP-37849 (0, 1, or 3 mg/kg), and the NR2B-selective antagonist, Ro 25-6981 (0, 3, or 10 mg/kg), to alter (3 g/kg) ethanol-induced sleep time was measured in C57BL/6J mice and NR2A knockout (KO) mice. The results show that pretreatment with either antagonist significantly potentiated the sedative/hypnotic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
8
35
1
Order By: Relevance
“…Replicating and extending our earlier finding, NR2A KO mice showed normal sensitivity to the sedative/hypnotic effects of ethanol (Boyce- Rustay and Holmes 2005). There was a significant effect of ethanol dose (F2,37=121.94, P<.01) but not of genotype (ns) and no dose×genotype interaction (ns) for sleep time responses to ethanol.…”
Section: Nr2a Ko Mice Show Normal Ethanol-induced Sedation/ Hypnosissupporting
confidence: 79%
See 2 more Smart Citations
“…Replicating and extending our earlier finding, NR2A KO mice showed normal sensitivity to the sedative/hypnotic effects of ethanol (Boyce- Rustay and Holmes 2005). There was a significant effect of ethanol dose (F2,37=121.94, P<.01) but not of genotype (ns) and no dose×genotype interaction (ns) for sleep time responses to ethanol.…”
Section: Nr2a Ko Mice Show Normal Ethanol-induced Sedation/ Hypnosissupporting
confidence: 79%
“…Ethanol-induced sedation/hypnosis was assessed as previously described (Boyce- Rustay and Holmes 2005). The mouse was injected with 3 or 4 g/kg and placed into the supine position in a "V"-shaped chamber.…”
Section: Ethanol-induced Sedation/hypnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The hypnotic/sedative effects of ethanol were assessed by measuring sleep time, as described previously (Crabbe et al, 1981;Boyce-Rustay and Holmes, 2005). 5-HTTϩ/ϩ, ϩ/Ϫ, and Ϫ/Ϫ mice were placed in the supine position in "V"-shaped chambers immediately after intraperitoneal injection of 3.0 or 4.0 g/kg of ethanol (200 proof prepared in 0.9% saline to produce 20% v/v solutions).…”
Section: Methodsmentioning
confidence: 99%
“…Little is known, however, about the effects that acute ethanol administration has on neuronal function in this region. The N-methyl-D-asparate receptor (NMDAR) has been heavily implicated in the acute actions of ethanol in both behavioral (Boyce-Rustay and Holmes, 2005) and molecular studies (Roberto et al, 2004). NMDARs in the BNST have been specifically implicated in the regulation of stress and anxiety Pawlak et al, 2005), which have been suggested to be important in regulating ethanol-seeking behavior in humans and in animal models of alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%